The Development of teacher potential in structional management through STEM Education for Sepon secondary school, Nongvilay secondary school and Phoukham upper secondary schoolry school and Phoukham upper secondary school - LEUANGLISH, vilaisavanh; Phaysit, Nounthida; xayyavet, Silivanh; Sackbuavong, Koun; Philabout, Inpan (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research aims to 1) Specifically examine the current situation and expected needs for developing teachers' potential in STEM education at Sepon secondary school, Nongvilay secondary school, and Phoukham upper secondary school, and 2) Propose strategies for enhancing teachers' potential in STEM education at these schools. The population for this study consisted of the Head of School, School Academic Heads, and teachers from 83 schools, amounting to a total of 1,099 individuals. The sample group included the Head of School, School Academic Heads, and teachers from Sepon Secondary School, Nongvilay Secondary School, and Phoukham Upper Secondary School during the second semester of the 2023–2024 academic year. This group comprised 86 participants in total. Furthermore, in-depth interviews were conducted with 11 key informants, including administrators and department heads, selected through stratified random sampling. The research instrument was a validated dual-response questionnaire with a reliability coefficient of 0.78. Data analysis utilized statistical methods such as mean values, standard deviation, prioritization of necessary needs (PNI Modified), and content analysis. The Result fount that: 1) The current capacity of teachers to manage STEM education at Sepon Secondary School, Nongvilay Secondary School, and Phoukham Upper Secondary School is at a high level Mean = 3.52 S.D. = 0.24 Meanwhile, the expected condition for developing teachers' abilities to fully manage STEM education is also high level Mean= 4.17 S.D. = 0.26 2) Proposed guidelines for improving teachers' ability to manage STEM education include: (1) School administrators should promote teaching principles and curriculum design that encourage students to seek knowledge and solve problems systematically, as reflected in 11 comments. (2) Administrators should support the use of diverse teaching activities, as indicated by 8 comments. (3) They should encourage teachers to provide opportunities for students to express their opinions on various topics to assess their knowledge and understanding, as highlighted in 7 comments and (4) Teachers should implement various student assessment models in a structured sequence, as noted in 6 comments.